Unpredictable Sound Stress Model Causes Migraine-Like Behaviors in Mice With Sexual Dimorphism - Viero, Fernanda Tibolla; Rodrigues, Patrícia; Frare, Julia Maria; Da Silva, Náthaly Andrighetto Ruviaro; Ferreira, Marcella de Amorim; Da Silva, Ana Merian; Pereira, Gabriele Cheiran; Ferreira, Juliano; Pillat, Micheli Mainardi; Bocchi, Guilherme Vargas; Nassini, Romina; Geppetti, Pierangelo; et al. (Frontiers in Pharmacology, 2022)
Migraine represents one of the major causes of disability worldwide and is more prevalent in women; it is also related to anxiety symptoms. Stress, such as sound stress, is a frequently reported trigger in migraine patients, but the underlying mechanisms are not fully understood. However, it is known that patients with migraine have higher levels of plasma inflammatory cytokines and calcitonin gene-related peptide (CGRP). Stress mediated by unpredictable sound is already used as a model of painful sensitization, but migraine-like behaviors and sexual dimorphism have not yet been evaluated. This study characterized nociception and anxiety-related symptoms after the induction of sound stress in mice. C57BL/6 mice (20–30 g) were exposed to unpredictable sound stress for 3 days, nonconsecutive days. We observed enhanced plasma corticosterone levels on day 1 after stress induction. First, 7 days after the last stress session, mice developed hind paw and periorbital mechanical allodynia, grimacing pain behavior, anxiety-like symptoms, and reduced exploratory behavior. The nociceptive and behavioral alterations detected in this model were mostly shown in female stressed mice at day 7 post-stress. In addition, on day 7 post-stress nociception, these behaviors were consistently abolished by the CGRP receptor antagonist olcegepant (BIBN4096BS, 100 mg/kg by intraperitoneal route) in female and male stressed mice. We also demonstrated an increase in interleukine-6 (IL-6), tumor necrosis factor (TNF-α), and CGRP levels in stressed mice plasma, with female mice showing higher levels compared to male mice. This stress paradigm allows further preclinical investigation of mechanisms contributing to migraine-inducing pain.